FORMULATION AND EVALUATION OF TASTE MASKED FAST DISSOLVING TABLET OF PRAZOSIN HYDROCHLORIDE - Aher, Smita; Saudagar, Ravindranath; Chaudhari, Dhanshri (Journal of Drug Delivery and Therapeutics, 2018)
The objective of this study was to control the elevated blood pressure in the patient with sudden episode of high blood pressure having markedly reduced function ability and restlessness. In such a case rapid onset of action is required. Prazosin Hydrochloride is drug with short biological half life. The purpose of study is to mask the bitter taste of drug and provide rapid onset of action. Inclusion complex of drug and Î²-Cyclodextrin can prepare by kneading method to mask the bitter taste of drug. 32 full factorial design was implemented, direct compression method were used to prepare tablet. F2 batch among all other batches showed disintegration time 55 sec with 98.56%drug release within 5min. thus it can be concluded the fast dissolving tablet can be formulated for antihypertensive drug. Keyword: Prazosin Hydrochloride, Î²-Cyclodextrin, Kneading method, Inclusion Complex, Antihypertensive, Drug Release.